Perspective of non-taxpayers’ perceptions on issues of ethics and equity in tax compliance / Ho Juan Keng, Loo Ern Chen and Lim Kwee Pheng - Ho, Juan Keng; Loo, Ern Chen; Lim, Kwee Pheng (Accounting Research Institute (ARI) & Faculty of Accountancy, 2006)
This paper presents the findings pertaining to the perceptions of non-taxpayers on ethics and equity in relation to tax compliance. A majority of these nontaxpayers agreed that if they were taxpayers, they themselves would, and they also believe that most other individuals would consider tax compliance as legal and social obligations. They would also comply if they believe that they would be paying only their fair of tax and that the tax system is fair. However, they believe that most other individuals would likely not comply if these individuals considered that the taxes payable are too high; that taxpayers’ money are being misappropriated or spent on wasteful projects; that they are not getting a fair share of the benefits that are financed out of taxpayers’ money or that others are also not complying with their obligations. On the issues of under-reporting income; altering the incident of taxes and making fictitious claims for relief and expenses, in the context of ethics, although they considered such acts as unjustifiable, however, they believe that such acts are being practiced by most individuals.